Semi‑rigid Composite Beam‑to‑column Joints for Cold‑formed Steel Frames : Experimental and Numerical Study - Faisal, Amsyar; Cher, Siang Tan; Arizu, Sulaiman; Shahrin, Mohammad (Springer Nature, 2023)
An experimental and numerical study was performed to evaluate the structural behaviour of the semi-rigid composite cold-formed steel beam-to-column joints, in terms of its strength and stiffness. Five composite joints were subjected to different diameters of rebar (8 mm and 10 mm) with varying types of reinforcing bar (high-strength rebar, mild-strength rebar and high-strength steel wire mesh) and different thicknesses of concrete slab (100 mm and 125 mm). Isolated joint tests were dispensed to all specimens by using 100 kN capacity of hydraulic jack to induce axial point load. Non-linear finite element models were developed by using ABAQUS software for the joint configurations. A 3-D stress option with an eight-node linear brick element and no hourglass controls (C3D8) was proposed to simulate all steel and concrete components as it provided well analysis prediction with further simulation beyond ultimate load-bearing capacity. Good correlation was observed from comparison of both experimental and numerical results with strength ratios that ranged from 0.92 to 0.98. Ultimate strength was obtained by increasing the diameter of steel reinforcement, thickness of concrete slab and using high-strength steel reinforcing bar instead of mild-steel reinforcing bar and high-strength steel wire mesh.